The Relationship Between Communication Skills and Student Learning Activities with the IPAS Learning Outcomes of Grade IV Elementary School Students - Hasna Luthfiyah; Eka Titi Andaryani (Jurnal Penelitian Pendidikan IPA, 2025)
The ability to communicate functions as a guide for students in learning, while active learning leads to knowledge that is actively obtained in the learning process. Both have a great influence on optimal learning outcomes. Therefore, this study examines the relationship between communication skills and learning activity with the learning outcomes of science students in grade IV of SD Cluster Melati, Bulakamba District, Brebes Regency. The method used in this study is quantitative with a type of correlation. The research population consisted of 95 students in class IV. The sampling technique uses saturated sampling, with data collection through observation, interviews, questionnaires, and documentation. This study found that there was a strong relationship between communication skills and learning activity on students' social studies learning outcomes. It is recommended that teachers and schools work together to improve communication skills and learning activity through classroom learning and school activities to support the development of student learning outcomes.